Threshold Effects in Coral Reef Fisheries - Anne Sophie Crépin (Fondazione Eni Enrico Mattei (FEEM), 2003)
Coral reefs may naturally flip between coral-dominated and algae-dominated states, when species' stocks trespass some threshold levels. This essay uses a stylized model of a coral reef to show how fishing may induce flips towards more algae-dominated states. Threshold effects have consequences for fisheries management, which are analyzed for open access fisheries and sole ownership.
Keywords: Q22; Q29; 330; Multiple Steady States; Fisheries; Threshold Effects; Coral Reefs; Skiba Points; Meerestiere; Fischerei